Relationship between Ergosterol Concentrations in Wine Yeast and Sugar Fermentation at Different Temperatures - Venter, J.J.; van Vuuren, H.J.J.; Tromp, A.; Randal, J.H. (South African Journal of Enology and Viticulture, 2017)
The effect of cellular ergosterol on the fermentation ability of four different Saccharomyces cerevisiae wine yeast strains was studied. F rmentations were carried out at three temperatures and ergosterol concentrations determined at six fermentation stages. The lower ergosterol concentrations at the higher temperatures are ascribed to the higher growth rate of the yeast cells resulting in a more rapid dilution of the ergosterol. Growth of yeast during fermentation was linked with the ergosterol content of the cells. The ergosterol concentration of the yeast cells was not directly correlated to specific fermentation rates.